Prenatal Diagnosis of Penoscrotal Hypospadia in Third Trimester by Two- and Three-Dimensional Ultrasonography: A Case Report - Lívia Teresa Moreira Rios; Edward Araujo Júnior; Luciano Marcondes Machado Nardozza; Liliam Cristine Rolo; Alan Roberto Hatanaka; Antonio Fernandes Moron; Marília da Glória Martins (Case Reports in Urology)
Hypospadia is an abnormal development of the corpus spongiosum, that involves cavernosa urethra, as a result of an inadequate fusion of the urethral folds. The incidence ranges from 0.2 to 4.1 per 1,000 live births. Among the markers of hypospadia, isolated ventral or lateral curvature of the penis associated with shortening are the most important markers and, in severe cases, can result in the classic “tulip sign.” The diagnosis of hypospadia is uncommon unless there is a routine of detailed analysis of fetal genitalia morphology. The prenatal diagnosis is of great importance for genetic counseling and allows better planning of postnatal treatment. The three-dimensional ultrasonography (3DUS) in rendering mode enables better comprehension of the pathology by parents, facilitating postnatal planning. We report a case of penoscrotal hypospadia diagnosed at 33 weeks of gestation, suspected due to the absence of testicles in the scrotum and difficulty of penis visualization. We emphasize the findings of 3DUS and its importance in the pathology compression by parents.